Peran Guru Dalam Peningkatan Mutu Pendidikan di MA Darul Ulum Semarang - Rahmawati, Alisa; Janah, Fathul; Zalnur, Muhammad; Al Banjari, Faisal (Arfannur, 2024)
This article aims to describe the role of gudu in improving the quality of education at MA Darul Ulum Semarang, Ngaliyan District, Semarang City. This research uses qualitative research, with a naturalistic approach, research data collection is obtained using observation, interview, and documentation techniques. The data analysis steps carried out were using the Bogdan model analysis, namely reducing the data, presenting the data, and then concluding. As a result of this research, researchers found four findings including: 1) The role of teachers in improving the quality of education at MA Darul Ulum is that teachers who teach must be linear with their field. 2) Teachers prepare complete learning tools at MA Darul Ulum before starting learning 3) Teachers at MA Darul Ulum accept technological developments consciously so that they help to develop the quality of student education 4) Facilities and infrastructure are a challenge for teachers at MA Darul Ulum to improve quality of education